The impact of students' attitude and subjective norm on the behavioural intention to use services of banking system - Alqasa, Khaled Mohammed; Md Isa, Filzah; Othman, Siti Norezam; Zolait, Ali Hussein Saleh (Inderscience Enterprises Ltd., 2014)
This study examines the ability and application of the theory of reasoned action TRA in explaining the use of banking system in Yemen.It investigates the impact of two theoretical variables attitude and subjective norms, using a sample consists of university students, on individuals' intention to use banking services. The results of the study revealed a strong predictive power of the theory of reasoned action model to explain university students' behavioural intention to use banking services. Statistically, the finding demonstrated that there are significant and positive relationships between students' attitude, subjective norm as predictor variables on the criterion variable of behavioural intention to use banking services in the context of Yemen. This study adds to the literature by showing non-financial variables such as attitude and subjective norm, which are important in understanding the behavioural intentions toward using banking services. It also provides some theoretical and practical implication. This study is one of the few studies that used theory of reasoned action in the context of Yemen. Furthermore, it has proven its effectiveness in predicting the behavioural intention of students towards using banking services. In addition, the finding will help to design strategies to attract more customers to use the banking system.